Cyber attacks : protecting national infrastructure - Amoroso, Edward G. Author; Vacca, John R. (Waltham, MA : Butterworth-Heinemann, 2013)
"Ten basic principles that will reduce the risk of cyber attack to national infrastructure in a substantive manner"--
Machine generated contents note: Chapter One: Introduction Chapter Two: Deception Chapter Three: Separation Chapter Four: Diversity Chapter Five: Consistency Chapter Six: Validation Chapter Seven: Collection Chapter Eight: Correlation Chapter Nine: Obscurity Chapter Ten: Awareness Chapter Eleven: Response Appendix A: Case Studies Appendix B: National Requirements.
Keywords: Cyberterrorism -- United States -- Prevention; Computer networks -- Security measures; Cyberspace -- Security measures; Computer crimes -- United States -- Prevention; National security -- United States